Optimized vehicle front end for pedestrian protection and enhanced aerodynamic efficiency / Kausaiyah Venkatason … [et al.] - Venkatason, Kausalyah; Izaty, Nur Azia; Sivaguru, Shasthri; M. R, Nor Ilya (Division of Research and Industry Linkages, 2017)
This study proposes a method of achieving an optimized vehicle front-end profile for improved protection for both adult and child pedestrian group, which at the same time is able to avoid designs that may cause Run-over scenarios. Design of Experiment is used to generate computational samples. The models are designed using Catia software based on seven design parameters focusing on the frontal area only. These designs undergo the simulation of Ansys to obtain the drag coefficient, Cd. Next, head injury criteria, HIC results from the crash simulations are tabulated as the response functions and optimization is carried out using Genetic Algorithm method. The optimized vehicle front end profile for the child pedestrian is shown to be different from the adult pedestrian and the optimized profiles are shown to be mutually not applicable for safety. Furthermore Run-over scenario is observed in child pedestrian optimized profiles where it invalidates the optimization. The designs which fulfill both aspect, low Cd and low HIC values are classified as the optimized models. The significance of this project is to build a vehicle front end profiles which is simultaneously safe for both the adult and child pedestrian in the event of the frontal impact, and to ensure that the profile generated does not allow a Run-over scenario to take place as that is more fatal than the primary impact itself. The project can be taken to further heights by studying the impact scenario for different pedestrian statures and also ensuring that the proposed vehicle front end design is aerodynamically efficient. This project expected to provide a guideline parameters in the car manufacturing industries and widely introduced to this sector in order improve the safety factor for pedestrian group.